Analysis of the Availability of Pedestrian Facilities for Mode Shift in Supporting the Merak-Banten Transit-Oriented Development (TOD) Area - Furjatullah, Sarah Auliya; Irawan, Muhammad Zudhy; Mulyono, Agus Taufik (Jurnal Fondasi, 2023)
High accessibility is a challenge for Cilegon City, an area with high transportation demands due to increasing migration rates. Increasing the high accessibility of Cilegon City can be focused on integrating transportation nodes in the Merak area, namely the Merak Integrated Terminal, Merak Harbor, and Merak Station, especially pedestrian accessibility as one of the indicators in the TOD area development plan in Merak-Banten. This research focuses on the walking interest of users of transportation nodes at modal shift facilities, knowing the level of interest and performance of capital switching facilities that can support a walking claim. The results of field observations show that several modal shift facilities need to meet the minimum service standards. Based on the results of the crosstab analysis and the chi-square test, it is known that social, economic, and demographic characteristics are related to the respondent's walking interest in capital transfer facilities that comply with minimum service standards. The minimum service standards consider security, safety, and comfort. Based on the results of the analysis using the importance-performance analysis (IPA) method, it is known that there are modal transfer facilities with a high level of importance but a low level of performance, namely the construction of a pedestrian bridge, the slope of the stairs and the direction facilities. Based on these conditions, optimizing the mode transfer facility per minimum service standards is necessary. This effort can be carried out in collaboration between stakeholders, such as the government and operators responsible for the three nodes.